Research progress on the fanconi anemia signaling pathway in non-obstructive azoospermia - Xu, Haohui; Zhang, Yixin; Wang, Caiqin; Fu, Zhuoyan; Lv, Jing; Yang, Yufang; Zhang, Zihan; Qi, Yuanmin; Meng, Kai; Yuan, Jinxiang; Wang, Xiaomei (Frontiers in Endocrinology, 2024)
Non-obstructive azoospermia (NOA) is a disease characterized by spermatogenesis failure and comprises phenotypes such as hypospermatogenesis, mature arrest, and Sertoli cell-only syndrome. Studies have shown that FA cross-linked anemia (FA) pathway is closely related to the occurrence of NOA. There are FA gene mutations in male NOA patients, which cause significant damage to male germ cells. The FA pathway is activated in the presence of DNA interstrand cross-links; the key step in activating this pathway is the mono-ubiquitination of the FANCD2-FANCI complex, and the activation of the FA pathway can repair DNA damage such as DNA double-strand breaks. Therefore, we believe that the FA pathway affects germ cells during DNA damage repair, resulting in minimal or even disappearance of mature sperm in males. This review summarizes the regulatory mechanisms of FA-related genes in male azoospermia, with the aim of providing a theoretical reference for clinical research and exploration of related genes.